The Wheat Genome - Appels, Rudi; Eversole, Kellye; Feuillet, Catherine; Gallagher, Dusti (Compendium of Plant Genomes, 2024)
This open access book provides the first comprehensive coverage of the wheat genome sequence since the publication of the draft and reference sequences for bread wheat and durum wheat. It presents an overview and all aspects of the gold standard sequence of the bread wheat genome, IWGSC RefSeq v1.0 and its subsequent improvements through 2022 (IWGSC RefSeq v2.1), as well as the sequencing of multiple elite wheat varieties, durum wheat, and ancient wheat. The book provides a broad and extensive review of the resources, tools, and methodologies available for exploiting the wheat genome sequence for crop improvement and studying fundamental questions related to the structure, function, and evolution of the wheat genome. Wheat (Tritcum aestivum L.) is the most widely grown crop in the world, contributing approximately 20 percent of total calories and more protein in human diets than any other single source. This book is useful to students, teachers, and scientists in academia and industryinterested in gaining an understanding of the wheat genome and its application as well as plant scientists generally interested in polyploid plant species.